Measuring and Comparing Party Ideology in Nonindustrialized Societies: Taking Party Manifesto Research to Africa - Sebastian Elischer (German Institute of Global and Area Studies (GIGA), 2010)
Despite a growing interest in African political parties, no comparative analyses of political ideology in Africa have been undertaken to date. This study addresses this shortcoming by applying the Manifesto Research Group's (MRG) coding scheme to a complete set of African party manifestos in three African countries. The study's main aim is to determine whether a research tool that has been seminal in the study of Western politics can be used to study political parties in nonindustrialized societies. In a first step the study examines the extent to which African manifestos advance programmatic ideas. Although most parties fail to do so, results indicate drastic differences between parties. The study subsequently investigates how African parties position themselves on a right-left spectrum. Most parties show a bias towards the political Left. Finally, the study examines the stance of individual parties on specific policy issues such as democracy and human rights, education, corruption, youth and women, and intercommunal relations. The study argues that although the MRG scheme has been designed against the historical background of European politics, it can be applied to advance the study of African parties. – – Trotz einer wachsenden Anzahl von Studien, die sich mit den politischen Parteien Afrikas beschäftigen, wurde bislang keine systematische Analyse von afrikanischen Wahlprogrammen vorgenommen. Die vorliegende Studie wendet das Kodierschema der Manifesto Research Group (MRG) auf alle politisch signifikanten Parteien in drei afrikanischen Ländern an. Das Hauptinteresse besteht darin, herauszufinden, ob ein eurozentrisches politikwissenschaftliches Instrument gleichfalls für die Analyse von politischen Parteien in nicht-industrialisierten Ländern geeignet ist. In einem ersten Schritt untersucht die Studie den Anteil von programmatischen Aussagen in Wahlprogrammen. Obwohl dieser bei den meisten Parteien niedrig ist, sind deutliche Unterschiede zwischen den einzelnen Parteien festzustellen. Ferner wird gefragt, wie sich Parteien im europäischen Links-Rechts Schema positionieren. Die meisten Parteien zeigen eine moderate Vorliebe für das linke Spektrum. Schließlich wird auch die Haltung einzelner Parteien zu spezifischen Politikfeldern, wie z.B. Demokratie, Menschenrechte, Bildung, Korruption etc., betrachtet. Das Fazit aus dieser Studie lautet, dass das MRG-Schema - obwohl es vor dem historischen Hintergrund der europäischen Politik entwickelt wurde - durchaus für eine tiefere Analyse von afrikanischen Parteien geeignet ist.
Keywords: 300; social cleavages; political parties; Ghana; Kenya; Namibia; Parteiprogramm; Ideologie; Sozialforschung; Afrika; Entwicklungsländer